“Your Children Will Soon be Forgotten:”: 12 Years a Slave and the ‘Seeding’ of Black Motherhood - Aldridge, Leah (Journal of the Motherhood Initiative for Research and Community Involvement, 2024)
This paper investigates how the 2013 film 12 Years a Slave, through the character of Eliza, makes visible struggles associated with Black motherhood that persist today as interlocking systems and institutions of oppression. Although Eliza occupies the narrative periphery, her experience of sudden loss and grief feels current as modern Black mothers confront sudden familial separation, grief, the disparagement of Black women’s health, and societal forgetting of Black children. While liberalisms would have us embrace the idea that chattel slavery no longer affects modern American society, this article insists that those connections be attended to if we are to understand contemporary challenges to modern-day Black motherhood. Finally, this article asserts that Black motherhood be characterized as one that elevates traditions, such as kinship, nurtures collective families, and moves beyond surviving to thriving to ensure that our children not be forgotten.